Penerapan Pembelajaran TaRL Untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas XI SMAN 2 Mengwi - Rosanti, Asih; I Komang Sukendra (Program Studi Pendidikan Matematika dan Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2025)
TaRL (Teaching at the Right Level) is a learning approach that does not focus on class level, but rather focuses on the level of cognitive ability of each student in the class. This approach provides students with the opportunity to learn according to their cognitive abilities by forming discussion groups based on low, medium and high ability levels, not based on class level or age. The aim of this research is to improve students' mathematics learning outcomes through the application of learning using the TaRL approach and the PBL learning model for class XI-G students at SMAN 2 Mengwi on statistics material for the 2023/2024 academic year. This type of research is Classroom Action Research (PTK) with two cycles. The harvest cycle consists of planning, implementing evacuation and reflection. The subjects of this research were students in class XI-G of SMAN 2 Mengwi in the 2023/2024 academic year. The data collection instruments used in this research were observation sheets, interviews and tests. The results of the research showed that in cycle I the percentage of students who completed was 50% then increased in cycle II with a completion percentage of 77%, because they had fulfilled the specified classical completeness, the research was stopped in cycle II. Based on these results, it can be concluded that there has been an increase in students' mathematics learning outcomes in statistics material by implementing learning using the TaRL approach.